A new fossil dolphin Dilophodelphis fordycei provides insight into the evolution of supraorbital crests in Platanistoidea (Mammalia, Cetacea) - Boersma, Alexandra T. (R Soc Open Sci, 2017)
Many odontocete groups have developed enlarged facial crests, although these crests differ in topography, composition and function. The most elaborate crests occur in the South Asian river dolphin (Platanista gangetica), in which they rise dorsally as delicate, pneumatized wings anterior of the facial bones. Their position wrapping around the melon suggests their involvement in sound propagation for echolocation. To better understand the origin of crests in this lineage, we examined facial crests among fossil and living Platanistoidea, including a new taxon, Dilophodelphis fordycei, nov. gen. and sp., described herein, from the Early Miocene Astoria Formation of Oregon, USA. We measured the physical extent and thickness of platanistoid crests, categorized their relative position and used computed tomography scans to examine their internal morphology and relative bone density. Integrating these traits in a phylogenetic context, we determined that the onset of crest elaboration or enlargement and the evolution of crest pneumatization among the platanistoids were separate events, with crest enlargement beginning in the Oligocene. However, we find no evidence for pneumatization until possibly the Early Miocene, although certainly by the Middle Miocene. Such an evolutionary context, including data from the fossil record, should inform modelling efforts that seek to understand the diversity of sound generation morphology in Odontoceti.